Occurrence of Fusarium spp. in Maize Grain Harvested in Portugal and Accumulation of Related Mycotoxins during Storage - Bruna Carbas; Daniela Simões; Andreia Soares; Andreia Freitas; Bruno Ferreira; Alexandre R. F. Carvalho; Ana Sanches Silva; Tiago Pinto; Eugénio Diogo; Eugénia Andrade; Carla Brites (Foods, 2021)
Maize is an important worldwide commodity susceptible to fungal contamination in the field, at harvest, and during storage. This work aimed to determine the occurrence of Fusarium spp. in maize grains produced in the Tagus Valley region of Portugal and the levels of related mycotoxins in the 2018 harvest and during their storage for six months in barrels, mimicking silos conditions. Continuous monitoring of temperature, CO2, and relative humidity levels were done, as well as the concentration of mycotoxins were evaluated and correlated with the presence of Fusarium spp. F. verticillioides was identified as the predominant Fusarium species. Zearalenone, deoxynivalenol and toxin T2 were not found at harvest and after storage. Maize grains showed some variability in the levels of fumonisins (Fum B1 and Fum B2). At the harvest, fumonisin B1 ranged from 1297 to 2037 µg/kg, and fumonisin B2 ranged from 411 to 618 µg/kg. Fumonisins showed a tendency to increase (20 to 40%) during six months of storage. Although a correlation between the levels of fumonisins and the monitoring parameters was not established, CO2 levels may be used to predict fungal activity during storage. The composition of the fungal population during storage may predict the incidence of mycotoxins.